Suggestions for International Students in the US - Gaulee, Uttam (Journal of International Students, 2015)
For international students transitioning into the US academic and social culture, as well as for those aspiring to make USA their higher education destination, Paras’ book is a savvy guide and companion. The book provides a detailed guidance in an illustrative manner for aspiring international students on critical steps from the beginning of the admission process to documentation, travel, and transition. The way Paras has chronicled a lived experience of a successful student himself, is commendable.